Asia-Pacific multicentre randomized trial of laparoscopic versus open major hepatectomy for hepatocellular carcinoma (AP-LAPO trial). Issue 1 (28th February 2023) - Ng, Kelvin K C; Chong, Charing C N; Lee, Kit-Fai; Lai, Paul B S; Cheng, Thomas K C; Chen, Hua-Wei; Yi, Bin; Huang, Ji-Wei
Abstract: Background: Hepatocellular carcinoma is the sixth most common malignancy in the world. Major hepatectomy (resection of greater than or equal to three liver segments) is needed if a tumour is large or close to major blood vessels. Despite low mortality, open major hepatectomy is associated with high rates of tumour recurrence that limits survival. Laparoscopic major hepatectomy has been proposed as an alternative approach with potential oncological benefits. This study compares laparoscopic major hepatectomy with open major hepatectomy for hepatocellular carcinoma in a randomized trial. Methods: The Asia-Pacific multicentre randomized trial of laparoscopic versus open major hepatectomy for hepatocellular carcinoma (AP-LAPO trial) is an open-labelled multicentre randomized trial to be conducted in five centres in the Asia-Pacific region. The study will test the hypothesis that laparoscopic major hepatectomy for hepatocellular carcinoma is associated with less tumour recurrence and better survival compared with open major hepatectomy; the primary outcome being 2-year recurrence-free survival. Secondary outcomes include hospital mortality, postoperative complications according to the Clavien–Dindo classification, time to functional recovery, quality of life, long-term survival, and postoperative serum surgical stress-related cytokines. Results and conclusion: The AP-LAPO trial will determine whether laparoscopic major hepatectomy offers oncological benefits to patients with hepatocellular carcinoma compared with open major hepatectomy. Registration number: NCT04852211 (http://www.clinicaltrials.gov ) registered on 21 April 2021 Protocol version: AP-LAPO trial version 01 (1 December 2021) Abstract : The AP-LAPO trial will be the first multicentre randomized trial evaluating the long-term oncological benefits of LMH for HCC. It provides level 1 evidence on the best surgical approach of major hepatectomy for HCC.